The Influence of Electronic Word of Mouth and Brand Image on Purchase Decisions of Aqua Mineral Water in Bandar Lampung - Nur Ishmah Aziizah; Satria Bangsawan; Mutiasari Nur Wulan (International Forum of Researchers and Lecturers, 2026)
Consumer behavior has changed as a result of the growth of social media and digital communication; consumers now look for information before making selections about what to buy, including mineral water goods. The growing influence of electronic word-of-mouth and the significance of brand image in shaping customer purchasing decisions are characteristics of this phenomenon. The purpose of this study is to examine how brand image and electronic word-of-mouth affect Bandar Lampung consumers' decisions to buy Aqua items. This study employs a survey method in conjunction with a quantitative approach. Purposive sampling was used to choose a sample of 150 Aqua customers in Bandar Lampung who completed questionnaires that were used to gather data. Multiple linear regression was used to analyze the data with the use of SPSS 27 software. The findings demonstrate that brand image and electronic word-of-mouth have a favorable and substantial impact on Bandar Lampung consumers' decisions to buy Aqua items. Additionally, brand image has a greater impact on purchase decisions than electronic word-of-mouth, suggesting that brand image has a greater influence on customer choices.